Tin bronze rod wire and preparation method thereof

By controlling the content of tin, P and Zn in the tin bronze alloy and adopting a specific process flow, the problems of dendrites segregation and excessive eutectics in the tin bronze alloy are solved, and high strength and good plasticity are achieved Tin bronze rod wire improves its mechanical properties.

CN119177373AActive Publication Date: 2024-12-24JINTIAN COPPER GROUP CORP NINGBO

Patent Information

Application Number
CN202411286003.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-24
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing tin bronze alloys have dendrite segregation and excessive α+δ+Cu3P ternary eutectics under high tin content, resulting in thermal brittleness, poor plasticity and poor processing performance, making it difficult to effectively improve mechanical properties.

Method used

By controlling the tin content between 10-14 wt%, the P content between 0.05-0.3 wt%, and the Zn content between 0.01-0.5 wt%, and using smelting → semi-continuous casting → homogenization annealing → hot extrusion → intermediate stretching and annealing → The process flow of finished product stretching → low-temperature annealing, control the proportion of α+δ+Cu3P ternary eutectics to form an optimized microstructure to improve mechanical properties.

Benefits of technology

The high strength and good plasticity of the tin bronze rod wire are achieved, the α+δ+Cu3P ternary eutectics are reduced, the grain size and shape are improved, and the overall performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177373A_ABST
    Figure CN119177373A_ABST
Patent Text Reader

Abstract

The invention discloses a tin bronze rod wire and a preparation method thereof. The tin bronze rod wire is prepared from the following components in percentage by weight: 10 to 14 weight percent of Sn, 0.05 to 0.3 weight percent of P, 0.01 to 0.5 weight percent of Zn and the balance of Cu and inevitable impurities. The structure of the tin bronze rod wire comprises an alpha + delta + Cu3P ternary eutectic, and the area proportion of the alpha + delta + Cu3P ternary eutectic is smaller than or equal to 0.5%. The tin bronze rod wire has good mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a tin bronze rod and wire material and a preparation method thereof. Background Art

[0002] Tin bronze is bronze with Sn as the main alloying element. The Sn content is generally between 2% and 14%, and it is mainly used to make elastic components, wear-resistant and corrosion-resistant parts. Tin bronze is a solid solution strengthening alloy. Sn plays a strong solid solution strengthening role in tin bronze. The mechanical properties of tin bronze increase with the increase of Sn content. The solidification temperature range of tin bronze alloy is wide. With the increase of Sn content, the problem of dendrite segregation in the cast structure is serious. A large amount of δ phase is distributed between the dendrites. The δ phase is composed of the electron compound Cu 31 Sn8-based solid solution has a complex cubic crystal structure, is hard and brittle, and cannot undergo plastic deformation. The δ phase in tin bronze will cause the plasticity of the alloy to decrease.

[0003] The invention patent application with publication number CN114875270A discloses a tin-phosphor bronze alloy, the mass percentage composition of which is Sn: 8.0-10.0%; P: 0.05-0.2%; In: 0.2-1.0%; Ni: 0.05-0.2%; Fe: ≤0.2%, other impurities: ≤0.2%, and the balance is Cu. The patent improves the cutting performance of the material by adding the In element to form easy-to-cut particles. Compared with Pb, In is environmentally friendly and harmless to human health on the one hand, and the alloy still maintains good processing plasticity and mechanical properties on the other hand, while also indirectly improving the electrical conductivity of the alloy. A tin-phosphor bronze alloy with excellent comprehensive performance is obtained through various methods such as solid solution strengthening, fine grain strengthening and work hardening. However, the tin-phosphor bronze alloy disclosed in the above patent has a high content of α+δ+Cu3P ternary eutectic, poor processing performance, and plasticity still needs to be further improved.

[0004] The invention patent application with publication number CN115404369A discloses a method for preparing a tin-phosphor bronze wire, wherein the mass percentage composition of the tin-phosphor bronze is Sn: 3.0-10.0wt%, P: 0.01-1.0wt%, and the balance is Cu and inevitable impurities; the preparation steps include: 1) smelting; 2) casting; 3) high temperature annealing; 4) hot extrusion: the extrusion temperature is 650-750℃, the extrusion speed is 3-6mm / s, and an extruded blank is obtained; 5) stretching and annealing. Through high temperature annealing and hot extrusion of the ingot, and controlling the relevant parameters, the δ phase is reduced, the hot extrusion blanking of the tin-phosphor bronze is achieved, and a dense blank is obtained, which lays the foundation for the subsequent stretching to obtain a tin-phosphor bronze wire with a smooth surface, and meets the requirements of the electronics, communications and other industries for high surface quality of the tin-phosphor bronze wire. However, the dendrite segregation of the tin-phosphor bronze wire is relatively serious, the content of the α+δ+Cu3P ternary eutectic is relatively high, and the strength and plasticity still have room for further improvement.

[0005] Since tin bronze usually needs to add a certain amount of P to improve the casting performance and mechanical properties of the alloy, α+δ+Cu3P ternary eutectic often appears in the cast structure of high-tin bronze, and its melting point is about 628℃. The presence of ternary eutectic makes the alloy exhibit hot brittleness. Therefore, high-tin bronze is prone to cracking during hot processing. It is usually produced by horizontal continuous casting. Although the ingots produced by horizontal continuous casting can be cold processed, the plasticity of the ingots is poor due to the large number of defects in the cast structure and the presence of ternary eutectic. Even if the ingots are subjected to high-temperature homogenization treatment, the ternary eutectic can only be reduced to a certain extent. Moreover, after the ingots are homogenized at high temperature for a long time, the structure of the ingots becomes very coarse. During the cold processing deformation process of the ingots, the orange peel phenomenon on the surface of the rods is serious. When the deformation degree is large, the surface of the rods cracks, the processing performance is poor, and the work hardening effect cannot be well utilized to obtain excellent mechanical properties. Summary of the invention

[0006] The invention provides a tin bronze rod and wire material, which has good mechanical properties.

[0007] The invention provides a tin bronze rod and wire, which is composed of the following components in weight percentage: Sn: 10-14wt%, P: 0.05-0.3wt%, Zn: 0.01-0.5wt%, and the balance is Cu and inevitable impurities;

[0008] The microstructure of the tin bronze rod and wire includes an α+δ+Cu3P ternary eutectic, and the area proportion of the α+δ+Cu3P ternary eutectic is ≤0.5%.

[0009] Sn: Sn has a strong solid solution strengthening effect in copper. As the Sn content increases, the strength of tin bronze also increases. When the Sn content exceeds 14%, the number of δ phases increases, the size becomes larger, and even δ phase agglomeration occurs. The plasticity of tin-phosphor bronze decreases significantly, the cold working performance deteriorates, and it is difficult to obtain high strength through work hardening. Therefore, the Sn content of the tin bronze of the present invention is in the range of 10-14%.

[0010] P: P can improve the wear resistance and casting properties of tin bronze. P can also be used as a deoxidizer to effectively reduce and control the formation of hard and brittle phase SnO2, thereby improving the mechanical properties of tin bronze. When the P content exceeds 0.3wt%, P forms Cu3P with Cu, and Cu3P forms a large amount of α+δ+Cu3P ternary eutectic with α phase and δ phase, and its melting point is about 628℃. The presence of ternary eutectic makes the alloy hot brittle and cracks easily during hot working; when the P content is lower than 0.05%, the effect of P on improving the casting and mechanical properties of the alloy is very weak, so the P content in the tin bronze of the present invention should be controlled at 0.05-0.3wt%.

[0011] Zn: The addition of Zn can narrow the crystallization temperature range of tin bronze, improve the fluidity of the alloy in the liquid state, and reduce dendrite segregation. Zn can also be dissolved in a large amount in the α phase of tin bronze to improve the mechanical properties of tin bronze, while having almost no effect on the alloy structure. However, when the Zn content exceeds 0.5wt%, the corrosion resistance of tin bronze is affected. Therefore, the Zn content in the tin bronze of the present invention should be controlled at 0.01-0.5wt%.

[0012] Preferably, the structure of the tin bronze rod and wire further includes twins, and the area of ​​the twins accounts for 30-55%.

[0013] Twins are two crystals that form a mirror-symmetrical orientation relationship along a common crystal plane. Twins are an important strengthening method for metal materials. For face-centered cubic metal materials, a high proportion of twins can increase the strength of the material, but too high a proportion will make the material brittle. Moderate deformation is conducive to the formation of annealing twins.

[0014] Preferably, the unavoidable impurities include Mn and Si, wherein Mn≤0.005wt%, Si≤0.005wt%.

[0015] Mn and Si are easily oxidized to generate metal oxides. Mn and Si with higher contents can reduce the fluidity of the alloy melt and easily cause dendrite segregation at a higher tin content. Therefore, the present invention controls the content of Mn and Si to an extremely low range.

[0016] The selection and control of chemical composition has a direct impact on the formation and proportion of twins. Different chemical compositions may lead to differences in crystal structure, which in turn affects the formation and proportion of twins.

[0017] Preferably, the average grain size of the tin bronze rod and wire is 3-15 μm. The grain size has a great influence on the mechanical properties and processing properties of the metal. Generally, the finer and more uniform the grains are at room temperature, the better the comprehensive performance of the material. However, if the grain size is too small, the total area of ​​the grain boundary is larger, the more dislocation barriers there are, the more grains with different orientations need to be coordinated, and the higher the resistance to plastic deformation of the metal. Too small a grain size limits the improvement of the processing rate of the rod and wire during cold processing.

[0018] Preferably, the average aspect ratio of the grains of the tin bronze rod and wire is 1 to 1.4. The aspect ratio of the grains refers to the ratio of the length of the grain to its diameter. The closer this value is to 1, the closer the grain shape is to equiaxed grains. Equiaxed grains have smaller size differences in all directions and have better mechanical properties than long grains.

[0019] Further preferably, the average aspect ratio of the grains of the tin bronze rod and wire is 1-1.2, and the structure of the tin bronze rod and wire further includes twins, and the area proportion of the twins is 36-55%.

[0020] On the other hand, the present invention also provides a method for preparing the tin bronze rod and wire, the process flow of the preparation method is: smelting → semi-continuous casting → first homogenization annealing → hot extrusion → second homogenization annealing → intermediate stretching and annealing → finished product stretching → low temperature annealing;

[0021] Wherein, the ingredients are prepared and smelted according to the mass percentage of each component of the tin bronze rod and wire;

[0022] The temperature of the second homogenization annealing is 600-680°C, and the holding time is 4-6 hours. When the holding time is less than 4 hours, the α+δ+Cu3P eutectic structure is still relatively large. When the holding time exceeds 6 hours, the grains grow so that the grain size exceeds 15 μm.

[0023] Preferably, the intermediate stretching and annealing comprises a first stretching, a second stretching and a third stretching, each of which has a processing rate of 30-45%.

[0024] The present invention not only enables the grains to obtain higher distortion energy through tensile deformation at a medium processing rate, but also further reduces the α+δ+Cu3P eutectic structure after annealing. In addition, annealing after deformation at a medium processing rate can promote the formation of twins.

[0025] Further preferably, the blank after the first stretching is subjected to a first intermediate annealing, wherein the temperature of the first intermediate annealing is 520-600° C. and the holding time is 2-4 hours;

[0026] The second intermediate annealing is performed on the blank after the second stretching, wherein the temperature of the second intermediate annealing is 400-490° C. and the holding time is 2-4 hours;

[0027] The third intermediate annealing is performed on the blank after the third stretching, wherein the temperature of the third intermediate annealing is 330-390° C. and the holding time is 3-6 hours.

[0028] After each stretching and intermediate annealing, the content of α+δ+Cu3P eutectic structure will be further reduced. Therefore, in order to better control the grain size, the intermediate annealing temperature forms a gradient change, so that while reducing the content of α+δ+Cu3P eutectic structure, the tin bronze rod and wire provided by the present invention has a better grain size.

[0029] During the tensile deformation process, the annealing temperature and holding time affect the effect of reducing the α+δ+Cu3P eutectic structure. The higher the temperature and the longer the holding time, the better the effect, but the grain size will grow. Therefore, the first annealing is performed at a high temperature with a holding time of 2-4h. The second and third annealing temperatures are gradually reduced to further reduce the α+δ+Cu3P eutectic structure, but the main purpose is to control the grain size. Due to the low temperature of the third annealing, the recrystallization is fully completed by appropriately extending the time.

[0030] Preferably, the smelting temperature is 1100-1300°C, the raw materials are electrolytic plates, tin ingots and Cu-P master alloys, and a modifier is added to the copper water. The modifier is a mixture of one or more of La / Ce mixed rare earths, Cu-Zr master alloys, and Cu-Ti master alloys, and the total addition amount is 0.04-0.2wt%.

[0031] The modifier added in the present invention promotes solidification nucleation and inhibits the growth of columnar crystals. If the modifier is added in an amount exceeding 0.2wt%, loose defects will be generated in the ingot structure, resulting in reduced performance.

[0032] Preferably, the semi-continuous casting is a vertical semi-continuous casting method, wherein the casting temperature is 1160-1280°C, the cooling water inlet temperature is 20-35°C, the cooling water pressure is 0.2-0.5Mpa, and the cooling water flow rate is 10-18m 3 / h, water outlet temperature: 25-45℃, casting speed: 40-80mm / min.

[0033] Preferably, the temperature of the first homogenization annealing is 700-800° C., and the holding time is 5-8 hours.

[0034] The tin bronze with high tin content provided by the present invention will produce serious dendrite segregation during solidification. The purpose of homogenization annealing is to reduce the dendrite segregation. Since Sn diffuses slowly in copper, in order to accelerate atomic diffusion, the homogenization annealing temperature is as high as possible to shorten the homogenization annealing time. In the present invention, due to the high Sn content, the dendrite segregation is more serious, the homogenization annealing temperature is 700-800°C, and the insulation time after reaching the temperature is 5-8h.

[0035] Preferably, the extrusion temperature of the hot extrusion is 700-860°C, and the extrusion speed of the hot extrusion is: the extrusion speed is 2-4 mm / s when the ingot extrusion is 20-35% completed, the extrusion speed is 4-7 mm / s when the ingot extrusion is 35-65% completed, and the extrusion speed is 7-10 mm / s when the ingot extrusion is 70-85% completed.

[0036] Further preferably, the extrusion temperature of the hot extrusion is 780-860°C.

[0037] Preferably, the extrusion ratio of the hot extrusion is 10-120.

[0038] Since the present invention needs to regulate the ratio of α+δ+Cu3P ternary eutectic and twin ratio in the microstructure, on the one hand, increasing the extrusion temperature helps to reduce the number of α+δ+Cu3P ternary eutectic in the extruded structure; on the other hand, since the twin ratio increases with the increase of the recrystallization volume fraction, the higher the extrusion temperature, the faster the dynamic recrystallization process of the extrusion, and the more sufficient the degree of recrystallization, the present invention needs to adopt a higher extrusion temperature, but the extrusion temperature is too high, the extrusion is easy to crack, and the high-temperature extrusion cracking problem can be improved by reducing the extrusion speed. Therefore, the tin bronze of the present invention should adopt a high-temperature and low-speed extrusion process, preferably the extrusion temperature is 780-860℃, and the extrusion setting speed is dynamically adjusted, the ingot extrusion speed is 2-4mm / s at the beginning, the ingot extrusion is completed 35-65%, the extrusion speed is adjusted to 4-7mm / s, the ingot extrusion is completed 70-85%, and the extrusion speed is adjusted to 7-10mm / s. The extrusion ratio provided by the present invention is 10-120. When the extrusion ratio is lower than 10, due to the low degree of extrusion deformation, the extruded billet may retain part of the cast structure, and the processing performance of the extruded billet deteriorates.

[0039] Preferably, the processing rate of the finished product stretching is above 40%. The purpose of the finished product stretching is to obtain high mechanical properties through work hardening.

[0040] Preferably, the low-temperature annealing temperature is 180-260° C., the heating time is 30-60 min, and the heat preservation time is 120-300 min.

[0041] The strength of the stretched rods and wires is further improved by low-temperature annealing. This is because low-temperature annealing reduces the number of movable dislocations inside the material, and the Sn atoms are segregated on the stacking fault plane and orderly strengthened. The low-temperature annealing temperature is 180-260℃, and the time from room temperature to this temperature is 30-60min, and the holding time is 120-300min. If the annealing temperature is too low, the number of movable dislocations will not decrease. If the annealing temperature is too high and exceeds the starting recrystallization temperature of the alloy, it will not only not increase the strength of the alloy, but also reduce the strength of the alloy due to recrystallization. If the heating time is too short, although the temperature controller has lowered the heating power, the heating of the resistance wire is delayed, causing the actual temperature of the furnace to temporarily exceed the set temperature, and then slowly drop to the set temperature. The period of time exceeding the set temperature will cause the material properties to change. If the heating time is too long, it is equivalent to an extended holding time, which also causes the material properties to change. If the holding time is too short, the strength increase is small, and if the holding time is too long, the strength may decrease.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention controls the tin content at a higher level, so that the strength of the tin bronze rod and wire provided by the present invention is higher. At a higher tin content, the present invention can also control the proportion of the α+δ+Cu3P ternary eutectic to not exceed 0.5%, so that the tin bronze rod and wire provided by the present invention has better plasticity.

[0044] In the process of preparing tin bronze rods and wires, a large amount of α+δ+Cu3P ternary eutectics are eliminated through the first homogenization annealing and hot extrusion, and then the remaining α+δ+Cu3P ternary eutectics are further eliminated by controlling the temperature and annealing time of the second homogenization annealing, so that the area proportion of the α+δ+Cu3P ternary eutectics does not exceed 0.5%, and at the same time a good grain size can be guaranteed to obtain a tin bronze rod and wire with good strength and plasticity. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a metallographic structure photograph of the tin bronze rod and wire prepared in Example 4 of the present invention;

[0046] Figure 2 This is a metallographic photograph of the tin bronze rod and wire provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer shall be followed.

[0048] The technical solution of the present application is described in detail below using an embodiment. The tensile strength Rm and yield strength Rp in the embodiment are 0.2 And elongation A50: tested in accordance with GB / T228.1-2021 "Metallic Materials Tensile Test Part 1: Room Temperature Test Method". The phase ratio, twin ratio, grain size and aspect ratio in the embodiments were observed under a metallographic microscope.

[0049] Example 1

[0050] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:

[0051] 1) Melting and casting: The ingredients are prepared according to the required alloy composition, and the electrolytic plate, tin ingot, and Cu-P master alloy are added to the electric furnace in sequence. The melting temperature is 1145-1255°C. After all the metals are melted and the alloy composition is tested to be qualified, a grain refiner is added, and the addition amount is 0.074wt%. Then the furnace head is tilted, and the ingot is cast by a vertical semi-continuous casting method. The casting temperature is 1180-1240°C, the cooling water inlet temperature is 20°C, the cooling water pressure is 0.45Mpa, the cooling water flow rate is 13.8m3 / h, the water outlet temperature is 30°C, the casting speed is 70mm / min, and the ingot specifications are

[0052] 2) Homogenization annealing: In order to accelerate atomic diffusion and shorten the homogenization annealing time, the homogenization annealing temperature is as high as possible, the homogenization annealing temperature is 740°C, and the holding time after reaching the temperature is 5.5h.

[0053] 3) Extrusion: high temperature and low speed extrusion process is adopted, the extrusion temperature is 800℃, and the extrusion setting speed is adjusted dynamically. The extrusion speed of the ingot is 4mm / s at the beginning, the extrusion speed is adjusted to 6mm / s when the ingot extrusion is about 35-65%, and the extrusion speed is adjusted to 10mm / s when the ingot extrusion is about 70-85%. The specifications of the extruded billet are The extrusion ratio is 32.

[0054] 4) Homogenization annealing: A lower homogenization annealing temperature should be used. The homogenization annealing temperature of the extruded billet is 670°C, the heating time is 1h, the holding time after reaching the temperature is 5h, and it is cooled to below 200°C and then taken out of the furnace.

[0055] 5) Intermediate stretching and annealing: The extruded billet is stretched to The processing rate is 32.4%, the intermediate annealing temperature is 600℃, the heating time is 1.5h, and the holding time is 4h; After the second stretch to The processing rate is 34.3%, the intermediate annealing temperature is 490℃, the heating time is 1h, and the holding time is 3.5h; After the third stretch to The processing rate is 30.6%, the intermediate annealing temperature is 390°C, the heating time is 0.5h, and the holding time is 5h.

[0056] 6) Finished product stretching: The blank is stretched to For bars, the processing rate is 48.2%.

[0057] 7) Low temperature annealing: The annealing temperature of the rod is 190℃, the time from room temperature to this temperature is 0.5h, and the holding time is 5h. The rod needs to be straightened after low-temperature annealing.

[0058] 8) Inspection.

[0059] Example 2

[0060] The difference from Example 1 is that the second homogenization annealing temperature and the annealing temperature after the middle three stretchings are lowered, and the rest is the same as Example 1. The influence of the homogenization annealing temperature and the annealing temperature after the middle three stretchings on the proportion of α+δ+Cu3P eutectic is investigated.

[0061] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:

[0062] 1) Melting and casting: The ingredients are prepared according to the required alloy composition, and the electrolytic plate, tin ingot, and Cu-P master alloy are added to the electric furnace in sequence. The melting temperature is 1145-1255°C. After all the metals are melted and the alloy composition is tested to be qualified, a grain refiner is added, and the addition amount is 0.074wt%. Then the furnace head is tilted, and the ingot is cast by a vertical semi-continuous casting method. The casting temperature is 1180-1240°C, the cooling water inlet temperature is 20°C, the cooling water pressure is 0.45Mpa, the cooling water flow rate is 13.8m3 / h, the water outlet temperature is 30°C, the casting speed is 70mm / min, and the ingot specifications are

[0063] 2) Homogenization annealing: In order to accelerate atomic diffusion and shorten the homogenization annealing time, the homogenization annealing temperature is as high as possible, the homogenization annealing temperature is 740°C, and the holding time after reaching the temperature is 5.5h.

[0064] 3) Extrusion: high temperature and low speed extrusion process is adopted, the extrusion temperature is 800℃, and the extrusion setting speed is adjusted dynamically. The extrusion speed of the ingot is 4mm / s at the beginning, the extrusion speed is adjusted to 6mm / s when the ingot extrusion is about 35-65%, and the extrusion speed is adjusted to 10mm / s when the ingot extrusion is about 70-85%. The specifications of the extruded billet are The extrusion ratio is 32.

[0065] 4) Homogenization annealing: A lower homogenization annealing temperature should be used. The homogenization annealing temperature of the extruded billet is 630°C, the heating time is 1h, the holding time after reaching the temperature is 5h, and it is cooled to below 200°C and then taken out of the furnace.

[0066] 5) Intermediate stretching and annealing: The extruded billet is stretched to The processing rate is 32.4%, the intermediate annealing temperature is 540℃, the heating time is 1.5h, and the holding time is 4h; After the second stretch to The processing rate is 34.3%, the intermediate annealing temperature is 450℃, the heating time is 1h, and the holding time is 3.5h; After the third stretch to The processing rate is 30.6%, the intermediate annealing temperature is 350°C, the heating time is 0.5h, and the holding time is 5h.

[0067] 6) Finished product stretching: The blank is stretched to For bars, the processing rate is 48.2%.

[0068] 7) Low temperature annealing: The annealing temperature of the rod is 190℃, the time from room temperature to this temperature is 0.5h, and the holding time is 5h. The rod needs to be straightened after low-temperature annealing.

[0069] 8) Inspection.

[0070] Example 3

[0071] The difference from Example 1 is that the second homogenization annealing holding time and the annealing holding time after the middle three stretching steps are reduced, and the rest is the same as Example 1. The influence of the homogenization annealing holding time and the annealing holding time after the middle three stretching steps on the proportion of α+δ+Cu3P eutectic is investigated.

[0072] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:

[0073] 1) Melting and casting: The ingredients are prepared according to the required alloy composition, and the electrolytic plate, tin ingot, and Cu-P master alloy are added to the electric furnace in sequence. The melting temperature is 1145-1255°C. After all the metals are melted and the alloy composition is tested to be qualified, a grain refiner is added, and the addition amount is 0.074wt%. Then the furnace head is tilted, and the ingot is cast by a vertical semi-continuous casting method. The casting temperature is 1180-1240°C, the cooling water inlet temperature is 20°C, the cooling water pressure is 0.45Mpa, the cooling water flow rate is 13.8m3 / h, the water outlet temperature is 30°C, the casting speed is 70mm / min, and the ingot specifications are

[0074] 2) Homogenization annealing: In order to accelerate atomic diffusion and shorten the homogenization annealing time, the homogenization annealing temperature is as high as possible, the homogenization annealing temperature is 740°C, and the holding time after reaching the temperature is 5.5h.

[0075] 3) Extrusion: high temperature and low speed extrusion process is adopted, the extrusion temperature is 800℃, and the extrusion setting speed is adjusted dynamically. The extrusion speed of the ingot is 4mm / s at the beginning, the extrusion speed is adjusted to 6mm / s when the ingot extrusion is about 35-65%, and the extrusion speed is adjusted to 10mm / s when the ingot extrusion is about 70-85%. The specifications of the extruded billet are The extrusion ratio is 32.

[0076] 4) Homogenization annealing: A lower homogenization annealing temperature should be used. The homogenization annealing temperature of the extruded billet is 670°C, the heating time is 1h, the holding time after reaching the temperature is 4h, and it is cooled to below 200°C and then taken out of the furnace.

[0077] 5) Intermediate stretching and annealing: The extruded billet is stretched to The processing rate is 32.4%, the intermediate annealing temperature is 600℃, the heating time is 1.5h, and the holding time is 2.5h; After the second stretch to The processing rate is 34.3%, the intermediate annealing temperature is 490℃, the heating time is 1h, and the holding time is 2.5h; After the third stretch to The processing rate is 30.6%, the intermediate annealing temperature is 390°C, the heating time is 0.5h, and the holding time is 3.5h.

[0078] 6) Finished product stretching: The blank is stretched to For bars, the processing rate is 48.2%.

[0079] 7) Low temperature annealing: The annealing temperature of the rod is 190℃, the time from room temperature to this temperature is 0.5h, and the holding time is 5h. The rod needs to be straightened after low-temperature annealing.

[0080] 8) Inspection.

[0081] Comparative Example 1

[0082] The chemical composition is controlled close to that of Example 1, and the conventional process route is: smelting→horizontal continuous casting Ф25→homogenization annealing (680°C / 6h)→stretching Ф18→straightening→inspection of the produced Ф18mm bars.

[0083] The mass percentages of the components of Examples 1-3 and Comparative Example 1 are shown in Table 1, and the microstructures are shown in Table 2.

[0084] Table 1 Chemical composition of Examples 1-3 and Comparative Example 1

[0085] serial number Sn P Zn Mn Si Cu Example 1 10.08 0.15 0.070 0.0041 0.0019 margin Example 2 11.42 0.22 0.021 0.0035 0.0026 margin Example 3 13.50 0.056 0.32 0.0033 0.0032 margin Comparative Example 1 10.13 0.16 0.073 0.0047 0.0021 margin

[0086] Table 2 Microstructure of Examples 1-3 and Comparative Example 1

[0087]

[0088] It can be seen from Tables 1 and 2 that the significant reduction in the proportion of α+δ+Cu3P eutectic and the appropriate grain size have a significant effect on the mechanical properties of tin bronze rods and wires. Compared with Comparative Example 1, when the proportion of α+δ+Cu3P eutectic is less than 0.5% and the average grain size reaches 3-15μm, the tin bronze rods and wires can achieve very high elongation and high mechanical properties.

[0089] Example 4

[0090] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:

[0091] 1) Melting and casting: The ingredients are prepared according to the required alloy composition, and the electrolytic plate, tin ingot, and Cu-P master alloy are added to the electric furnace in sequence. The melting temperature is 1160-1260°C. After all the metals are melted and the alloy composition is tested to be qualified, a grain refiner is added, and the addition amount is 0.09wt%. Then the furnace head is tilted, and the ingot is cast by a vertical semi-continuous casting method. The casting temperature is 1190-1250°C, the cooling water inlet temperature is 24°C, the cooling water pressure is 0.5Mpa, the cooling water flow rate is 15m3 / h, the water outlet temperature is 33°C, the casting speed is 65mm / min, and the ingot specifications are

[0092] 2) Homogenization annealing: In order to accelerate atomic diffusion and shorten the homogenization annealing time, the homogenization annealing temperature is as high as possible, the homogenization annealing temperature is 750°C, and the holding time after reaching the temperature is 6 hours.

[0093] 3) Extrusion: high temperature and low speed extrusion process is adopted, the extrusion temperature is 820℃, and the extrusion setting speed is adjusted dynamically. The extrusion speed of the ingot is 4mm / s at the beginning, the extrusion speed is adjusted to 6mm / s when the ingot extrusion is about 35-65%, and the extrusion speed is adjusted to 10mm / s when the ingot extrusion is about 70-85%. The specifications of the extruded billet are The extrusion ratio is 32.

[0094] 4) Homogenization annealing: A lower homogenization annealing temperature should be used. The homogenization annealing temperature of the extruded billet is 650°C, the heating time is 1h, the holding time after reaching the temperature is 4h, and it is cooled to below 200°C and then taken out of the furnace.

[0095] 5) Intermediate stretching and annealing: The extruded billet is stretched to The processing rate is 32.4%, the intermediate annealing temperature is 580℃, the heating time is 1.5h, and the holding time is 4h; After the second stretch to The processing rate is 34.3%, the intermediate annealing temperature is 470℃, the heating time is 1h, and the holding time is 3.5h; After the third stretch to The processing rate is 30.6%, the intermediate annealing temperature is 370°C, the heating time is 0.5h, and the holding time is 5h.

[0096] 6) Finished product stretching: The blank is stretched to For bars, the processing rate is 48.2%.

[0097] 7) Low temperature annealing: The annealing temperature of the rod is 200℃, the time from room temperature to this temperature is 0.5h, and the holding time is 5h. The rod needs to be straightened after low-temperature annealing.

[0098] 8) Inspection.

[0099] Example 5

[0100] One specification is The preparation method of high-strength tin-phosphor bronze wire is as follows:

[0101] 1) Melting and casting: The ingredients are prepared according to the required alloy composition, and the electrolytic plate, tin ingot, and Cu-P master alloy are added to the electric furnace in sequence. The melting temperature is 1140-1270°C. After all the metals are melted and the alloy composition is tested to be qualified, a grain refiner is added, and the addition amount is 0.15wt%. Then the furnace head is tilted, and the ingot is cast by a vertical semi-continuous casting method. The casting temperature is 1180-1240°C, the cooling water inlet temperature is 22°C, the cooling water pressure is 0.45Mpa, the cooling water flow rate is 13m3 / h, the water outlet temperature is 31°C, the casting speed is 80mm / min, and the ingot specifications are

[0102] 2) Homogenization annealing: In order to accelerate atomic diffusion and shorten the homogenization annealing time, the homogenization annealing temperature is as high as possible, the homogenization annealing temperature is 720℃, and the holding time after reaching the temperature is 7h.

[0103] 3) Extrusion: high temperature and low speed extrusion process is adopted, the extrusion temperature is 850℃, and the extrusion setting speed is adjusted dynamically. The extrusion speed of the ingot is 3mm / s at the beginning, the extrusion speed is adjusted to 5mm / s when the ingot extrusion is about 35-65%, and the extrusion speed is adjusted to 9mm / s when the ingot extrusion is about 70-85%. The specifications of the extruded billet are The extrusion ratio is 82.

[0104] 4) Homogenization annealing: A lower homogenization annealing temperature should be used. The homogenization annealing temperature of the extruded billet is 620°C, the heating time is 1h, the holding time after reaching the temperature is 4.5h, and it is cooled to below 200°C and then taken out of the furnace.

[0105] 5) Intermediate stretching and annealing: The extruded billet is stretched to The processing rate is 36%, the intermediate annealing temperature is 570℃, the heating time is 1.5h, and the holding time is 3h; After the second stretch to The processing rate is 34%, the intermediate annealing temperature is 450°C, the heating time is 1h, and the holding time is 3h; After the third stretch to The processing rate is 40.8%, the intermediate annealing temperature is 350°C, the heating time is 0.5h, and the holding time is 5h.

[0106] 6) Finished product stretching: The blank is stretched to Wire, processing rate is 64%.

[0107] 7) Low temperature annealing: The wire annealing temperature is 180°C, the time from room temperature to this temperature is 0.5h, and the holding time is 4h.

[0108] 8) Inspection.

[0109] Example 6

[0110] One specification is The preparation method of high-strength tin phosphor bronze rod is as follows:

[0111] 1) Melting and casting: The ingredients are prepared according to the required alloy composition, and the electrolytic plate, tin ingot, and Cu-P master alloy are added to the electric furnace in sequence. The melting temperature is 1180-1270°C. After all the metals are melted and the alloy composition is tested to be qualified, a grain refiner is added, and the addition amount is 0.06wt%. Then the furnace head is tilted, and the ingot is cast by a vertical semi-continuous casting method. The casting temperature is 1200-1260°C, the cooling water inlet temperature is 17°C, the cooling water pressure is 0.5Mpa, the cooling water flow rate is 16m3 / h, the water outlet temperature is 28°C, the casting speed is 55mm / min, and the ingot specifications are

[0112] 2) Homogenization annealing: In order to accelerate atomic diffusion and shorten the homogenization annealing time, the homogenization annealing temperature is as high as possible, the homogenization annealing temperature is 780°C, and the holding time after reaching the temperature is 6 hours.

[0113] 3) Extrusion: high temperature and low speed extrusion process is adopted, the extrusion temperature is 790℃, and the extrusion setting speed is adjusted dynamically. The extrusion speed of the ingot is 2mm / s at the beginning, the extrusion speed is adjusted to 4mm / s when the ingot extrusion is about 35-65%, and the extrusion speed is adjusted to 8mm / s when the ingot extrusion is about 70-85%. The specifications of the extruded billet are The extrusion ratio is 32.

[0114] 4) Homogenization annealing: A lower homogenization annealing temperature should be used. The homogenization annealing temperature of the extruded billet is 680°C, the heating time is 1h, the holding time after reaching the temperature is 5h, and it is cooled to below 200°C and then taken out of the furnace.

[0115] 5) Intermediate stretching and annealing: The extruded billet is stretched to The processing rate is 31.3%, the intermediate annealing temperature is 600℃, the heating time is 1.5h, and the holding time is 4h; After the second stretch to The processing rate is 31.5%, the intermediate annealing temperature is 490℃, the heating time is 1h, and the holding time is 3h; After the third stretch to The processing rate is 30.5%, the intermediate annealing temperature is 380°C, the heating time is 1h, and the holding time is 4.5h.

[0116] 6) Finished product stretching: The blank is stretched to For bars, the processing rate is 43.8%.

[0117] 7) Low temperature annealing: The annealing temperature of the rod is 200℃, the time from room temperature to this temperature is 0.5h, and the holding time is 5h. The rod needs to be straightened after low-temperature annealing.

[0118] 8) Inspection.

[0119] Example 7

[0120] One specification is The preparation method of high-strength tin-phosphor bronze wire is as follows:

[0121] 1) Melting and casting: The ingredients are prepared according to the required alloy composition, and the electrolytic plate, tin ingot, and Cu-P master alloy are added to the electric furnace in sequence. The melting temperature is 1135-1260°C. After all the metals are melted and the alloy composition is tested to be qualified, a grain refiner is added, and the addition amount is 0.18wt%. Then the furnace head is tilted, and the ingot is cast by a vertical semi-continuous casting method. The casting temperature is 1190-1250°C, the cooling water inlet temperature is 17°C, the cooling water pressure is 0.4Mpa, the cooling water flow rate is 12m3 / h, the water outlet temperature is 25°C, the casting speed is 70mm / min, and the ingot specifications are

[0122] 2) Homogenization annealing: In order to accelerate atomic diffusion and shorten the homogenization annealing time, the homogenization annealing temperature is as high as possible, the homogenization annealing temperature is 710℃, and the holding time after reaching the temperature is 6.5h.

[0123] 3) Extrusion: high temperature and low speed extrusion process is adopted, the extrusion temperature is 830℃, and the extrusion setting speed is adjusted dynamically. The extrusion speed of the ingot is 3.5mm / s at the beginning, the extrusion speed is adjusted to 6mm / s when the ingot extrusion is about 35-65%, and the extrusion speed is adjusted to 8mm / s when the ingot extrusion is about 70-85%. The specifications of the extruded billet are The extrusion ratio is 60.5.

[0124] 4) Homogenization annealing: A lower homogenization annealing temperature should be used. The homogenization annealing temperature of the extruded billet is 640°C, the heating time is 1h, the holding time after reaching the temperature is 4h, and it is cooled to below 200°C and then taken out of the furnace.

[0125] 5) Intermediate stretching and annealing: The extruded billet is stretched to The processing rate is 31.7%, the intermediate annealing temperature is 570℃, the heating time is 1.5h, and the holding time is 4h; After the second stretch to The processing rate is 35%, the intermediate annealing temperature is 450℃, the heating time is 1h, and the holding time is 3h; After the third stretch to The processing rate is 42.2%, the intermediate annealing temperature is 360°C, the heating time is 0.5h, and the holding time is 4.5h.

[0126] 6) Finished product stretching: The blank is stretched to Wire rod, processing rate is 50.8%.

[0127] 7) Low temperature annealing: The wire annealing temperature is 190°C, the time from room temperature to this temperature is 0.5h, and the holding time is 4h.

[0128] 8) Inspection.

[0129] Comparative Example 2: Purchase C5240 brand Ф18mm bars.

[0130] The mass percentages of the components of Examples 4-7 and Comparative Example 2 are shown in Table 3, and the microstructures are shown in Table 4.

[0131] Table 3 Chemical composition of Examples 4-7 and Comparative Example 2

[0132]

[0133] Table 4 Microstructure of Examples 4-7 and Comparative Example 2

[0134]

[0135] It can be seen from Tables 3 and 4 that a higher twin ratio and a suitable grain aspect ratio can improve the mechanical properties of tin bronze rods and wires. Under high tin content, controlling the content of harmful elements Mn and Si below 0.005wt% can better achieve higher mechanical properties.

[0136] like Figure 1 As shown, the average grain size is 12μm, the grains are small, and the average aspect ratio of the grains is 1.25, which is close to 1, indicating that the grains are close to equiaxed crystals. The twin ratio is 15.6%. Although the number of twins is small, the α+δ+Cu3P eutectic accounts for only 0.15%, which is almost invisible, reaching the control range of the present invention. The rod has excellent mechanical properties, ( Figure 1 Corresponding to Example 4).

[0137] like Figure 2As shown, the average grain size is 30μm, the grains are relatively coarse, and the average aspect ratio of the grains is 2.82, which is far from 1, indicating that the grains are non-equiaxed. The twin ratio is only 15.6%, and the number of twins is small. The α+δ+Cu3P eutectic (black dots) accounts for 5.73%, which exceeds 0.5%, and the number is large, which is beyond the control range of the present invention. The mechanical properties of the rod are poor. Figure 2 Corresponding to proportion 1).

Claims

1. A tin bronze rod and wire, characterized in that: The tin bronze rod and wire is composed of the following components in weight percentage: Sn: 10-14wt%, P: 0.05-0.3wt%, Zn: 0.01-0.5wt%, and the balance is Cu and unavoidable impurities; The microstructure of the tin bronze rod and wire includes an α+δ+Cu3P ternary eutectic, and the area proportion of the α+δ+Cu3P ternary eutectic is ≤0.5%.

2. The tin bronze rod and wire according to claim 1, characterized in that: The microstructure of the tin bronze rod and wire also includes twins, and the area of ​​the twins accounts for 30-55%.

3. The tin bronze rod and wire according to claim 1, characterized in that: The unavoidable impurities include Mn and Si, wherein Mn≤0.005wt%, Si≤0.005wt%.

4. The tin bronze rod and wire according to claim 1, characterized in that: The average grain size of the tin bronze rod and wire is 3-15 μm.

5. The tin bronze rod and wire according to claim 1, characterized in that: The average aspect ratio of the grains of the tin bronze rod and wire is 1-1.

4.

6. A method for preparing the tin bronze rod and wire according to any one of claims 1 to 5, characterized in that: The process flow of the preparation method is: smelting → semi-continuous casting → first homogenization annealing → hot extrusion → second homogenization annealing → intermediate stretching and annealing → finished product stretching → low-temperature annealing; Wherein, the ingredients are prepared and smelted according to the mass percentage of each component of the tin bronze rod and wire according to any one of claims 1 to 5; The temperature of the second homogenization annealing is 600-680° C., and the holding time is 4-6 hours.

7. The method for preparing tin bronze rod and wire according to claim 6, characterized in that: The intermediate stretching and annealing includes a first stretching, a second stretching and a third stretching, each of which has a processing rate of 30-45%.

8. The method for preparing tin bronze rod and wire according to claim 7, characterized in that: Performing a first intermediate annealing on the blank after the first stretching, wherein the temperature of the first intermediate annealing is 520-600° C. and the holding time is 2-4 hours; The second intermediate annealing is performed on the blank after the second stretching, wherein the temperature of the second intermediate annealing is 400-490° C. and the holding time is 2-4 hours; The third intermediate annealing is performed on the blank after the third stretching, wherein the temperature of the third intermediate annealing is 330-390° C. and the holding time is 3-6 hours.

9. The method for preparing tin bronze rod and wire according to claim 6, characterized in that: The extrusion temperature of the hot extrusion is 700-860°C, and the extrusion speed of the hot extrusion is: when the ingot extrusion is 20-35%, the extrusion speed is 2-4mm / s, when the ingot extrusion is 35-65%, the extrusion speed is 4-7mm / s, and when the ingot extrusion is 70-85%, the extrusion speed is 7-10mm / s.

10. The method for preparing tin bronze rod and wire according to claim 6, characterized in that: The temperature of the low-temperature annealing is 180-260° C., the heating time is 30-60 min, and the heat preservation time is 120-300 min.

Citation Information

Patent Citations

  • Preparation method of high-strength tin-phosphor bronze bar

    CN114737071A

  • Tin-phosphor bronze alloy and preparation method thereof

    CN114875270A

  • Preparation method of tin-phosphor bronze wire

    CN115404369A

  • Leadless bronze casting alloy

    JP2008208433A

Cited By

  • Tin-zinc bronze alloy and preparation method thereof

    CN120060695A

  • Preparation method of high-strength and high-toughness lead-tin bronze bar

    CN120138426A